Neurotrophic factors and hippocampal activity in PTSD - (:unkn) unknown (PUBLIC LIBRARY SCIENCE, 2018)
Although numerous studies have investigated the neurotrophic factors and hippocampal activity in posttraumatic stress disorder (PTSD) separately each other, it is unclear whether an association between neurotrophic factors and hippocampal activity is present. The aim of this study was to evaluate the functional changes in hippocampus before and after treatment with escitalopram and to associate these changes with peptides related to neuronal growth in patients with chronic PTSD and trauma survivors without PTSD. Fifteen earthquake survivors with chronic PTSD and thirteen drug nave trauma exposed individuals without PTSD underwent fMRI scans in a block design. Serum levels of Nerve Growth Factor (NGF) and Brain Derived Neurotrophic Factor (BDNF) were measured before and after 12 weeks treatment with escitalopram. Baseline median serum level of NGF was significantly lower in patients with chronic PTSD than trauma survivors; however, 12 weeks of treatment with escitalopram significantly increased it. Higher activation was found both in left and right hippocampus for chronic PTSD group than trauma survivors. Treatment with escitalopram was significantly associated with suppression of the hyperactivation in left hippocampus in patients with chronic PTSD. Bilateral hyperactivation in hippocampus and lowered NGF may associate with neurobiological disarrangements in chronic PTSD. Treatment with escitalopram was significantly associated with both improvement in the severity of PTSD symptoms and biological alterations. Patients diagnosed with PTSD may have further and complicated deteriorations in hippocampal networks and neurotransmitter systems than individuals who had not been diagnosed with PTSD following the same traumatic experience.
Keywords: POSTTRAUMATIC-STRESS-DISORDER; CHILDHOOD SEXUAL-ABUSE; SCRIPT-DRIVEN IMAGERY; CEREBRAL-BLOOD-FLOW; PSYCHOPHYSIOLOGICAL ASSESSMENT; TRAUMATIC MEMORIES; BRAIN ACTIVATION; SERUM-LEVELS; OPEN-LABEL; DEPRESSION